The Police Use of Force Mandate in West Africa - Norman, Ishmael (Advances in Social Sciences Research Journal, 2021)
This paper reviewed Police use of force mandate of the Constitutions of Ghana, Nigeria, Sierra Leone and Gambia, to determine if the mandate is a contributory factor for increased police killings. The evidence support the finding that, police policy on the use of force contributes to increased extralegal killings, in the absence of field protocols for its engagement. There is the need for clear articulation of how, when, where force may be applied to cause arrest or suppress crime or riot. This paper aims to contribute to knowledge on limiting the use of force abuses within West Africa.